Building Student Confidence Through Satisfaction : The Role Of Service Quality, Education Costs And Institutional Image In A-Acreditated Muhammadiyah Senior High School - Iis Dewi Fitriani; Popo Suryana; Nandan Limakrisna (International Journal of Artificial Intelligence Research, 2026)
Competition among private secondary education institutions in metropolitan areas requires schools to improve service quality to build student satisfaction and trust. This study aims to analyze the influence of service quality, tuition fees, and institutional image on student satisfaction and their impact on student trust at A-accredited Muhammadiyah Senior High Schools in the Bandung Metropolitan area. This study uses a quantitative approach with an explanatory survey method . The study population was all 4,674 A-accredited Muhammadiyah Senior High School students in the Bandung Metropolitan area, with a sample of 223 grade XII students determined through a two-stage sampling technique . Data collection was carried out using a Likert-scale questionnaire, interviews, and observations. Data analysis used Structural Equation Modeling (SEM). The results showed that service quality, tuition fees, and institutional image had a positive and significant effect on student satisfaction. Furthermore, student satisfaction had a positive and significant effect on student trust. Student satisfaction was also proven to mediate the influence of service quality, tuition fees, and institutional image on student trust. These findings confirm that improving service quality, proportional management of education costs, and strengthening the institution's image are strategic factors in building student satisfaction and trust at Muhammadiyah Senior High Schools accredited A in the Bandung Metropolitan area.